Influence of Annealing Conditions on Structure and Critical Parameters of Ni50Mn37Sn13 Magnetocaloric Material - Dan, Nguyen Huy; An, Nguyen Manh (Communications in Physics, 2014)
In this paper, we present the influence of annealing conditions on structure and magnetic behavior of Ni\(_50\)Mn\(_37\)Sn\(_13\) magnetocaloric alloy prepared by arc-melting technique. The results show that the almost single phase of the full Heusler structure of Ni\(_2\)MnSn could be achieved by appropriate annealing. The transformation between martensite and austenite phases, and multi-magnetic phase behavior are observed more clearly with higher fraction of Ni\(_2\)MnSn phase. By using Arrott-Noaks method, critical parameters were determined to be \(β 0.464 ± 0.021\), \(γ = 1.117 ± 0.073\) and \(δ = 3.41\), which lay between mean-field model (\(β = 0.5\) and \(γ = 1\), \(δ = 3\)) with long-range ferromagnetic orders and 3D Heisenberg model (\(β = 0.365\), \(γ = 1.336\), \(δ g= 4.66\)) with short-range ferromagnetic orders. The calculated results are in good accordance with the experimentally observed coexistence of weak-ferromagnetic martensite and strong-ferromagnetic austenite phases.